2001
DOI: 10.1590/s0066-782x2001000300005
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen therapy, continuous positive airway pressure, or noninvasive bilevel positive pressure ventilation in the treatment of acute cardiogenic pulmonary edema

Abstract: Noninvasive bilevel positive pressure ventilation was effective in the treatment of acute cardiogenic pulmonary edema, accelerated the recovery of vital signs and blood gas data, and avoided intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 17 publications
(20 reference statements)
2
36
0
5
Order By: Relevance
“…45,54,57,59,61,62 or all three of these treatments. 50,56,64,65 Before publication of a recent large RCT, 65 which accounted for 40% of all patients who have been studied in RCTs of continuous positive airway pressure for cardiogenic pulmonary edema and 70% of patients receiving noninvasive positive-pressure ventilation for this indication, five separate systematic reviews [162][163][164][165][166] had consistently demonstrated a significant reduction in endotracheal intubation with both types of noninvasive ventilation. When this large trial was included in the metaanalysis, there was a trend toward reduction in endotracheal intubation with noninvasive positive-pressure ventilation (RR 0.55, 95% CI 0.29-1.03) and a significant reduction in endotracheal intubation with continuous positive airway pressure by mask (RR 0.42, 95% CI 0.28-0.63) relative to oxygen alone.…”
Section: Cardiogenic Pulmonary Edemamentioning
confidence: 99%
“…45,54,57,59,61,62 or all three of these treatments. 50,56,64,65 Before publication of a recent large RCT, 65 which accounted for 40% of all patients who have been studied in RCTs of continuous positive airway pressure for cardiogenic pulmonary edema and 70% of patients receiving noninvasive positive-pressure ventilation for this indication, five separate systematic reviews [162][163][164][165][166] had consistently demonstrated a significant reduction in endotracheal intubation with both types of noninvasive ventilation. When this large trial was included in the metaanalysis, there was a trend toward reduction in endotracheal intubation with noninvasive positive-pressure ventilation (RR 0.55, 95% CI 0.29-1.03) and a significant reduction in endotracheal intubation with continuous positive airway pressure by mask (RR 0.42, 95% CI 0.28-0.63) relative to oxygen alone.…”
Section: Cardiogenic Pulmonary Edemamentioning
confidence: 99%
“…Continuous positive airway pressure is an effective treatment for the failing heart, not only because it inflates the lungs but also because it augments cardiac performance by decreasing pre and after load. 69,70 On the other hand, the recent observation that Cheyne-Stokes respiration is more frequent in the supine position is compelling evidence that upper airway instability does play a role in the aggravation of the respiration, at least in some patients.…”
Section: Contributing Factors To Respiratory Instabilitymentioning
confidence: 99%
“…Over the past three decades, application of noninvasive ventilation (NIV) either with continuous positive airway pressure (CPAP) or Bi-level positive airway pressure (Bi-PAP) has been used with the standardized medical treatment as an effective therapeutic approach to treat ACPE [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The goals of NIV use in the treatment of ACPE are to improve oxygenation, reduce the effort of breathing and increase cardiac output and decreased left ventricular preand after-load [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%